Afetividade e interatividade na educação a distância: dimensões dos processos educativos em cursos de graduação - Marina Rodrigues Ramos (2018)
This research aims to analyze how the relations of affectivity and interactivity in the processes involving the actors (student, teacher, tutor and team of professionals) of distance learning (EaD) are established and to what extent do these relationships lead to greater involvement, participation and engagement of the students in the educational activities developed. The problematization seeks to investigate how the relations of interactivity and affectivity in the processes involving the actors (student, teacher, tutor and team of professionals) of distance education? To what extent do these relationships lead to greater involvement, participation, and engagement of students in their activities? The theoretical framework was structured in order to understand the concept of affectivity and its implications. For this, a study of Vygostsky's theory was carried out, which deals with the question of affectivity through the study of the experiences and of Henri Wallon, which integrates affectivity, intelligence and motor act. Subsequently, the regulatory framework of EaD is presented based on legislation that regulates the modality and the issue of affectivity in the educational processes is explored, taking as reference Freire (1996) and Vygostsky (1993). Based on authors such as Peters (2006), Moore and Kersley (2008), Marco Silva (2014), Lilian Valle and Estrella Bohadana (2012), the last theoretical chapter presents the concept of dialogue, interaction and interactivity in distance education. The empirical research was obtained in a bachelors degree in Administration, offered by a private university and a degree in Pedagogy offered by a public university linked to the Open University of Brazil (UAB) system. The methodological procedures were semi-structured interviews and questionnaires with a representative sample of students enrolled in the courses. The data were analyzed from the perspective of Laurence Bardin's content analysis. Two analytical categories were chosen: the first dialogue, interaction and interactivity, and the second affectivity, in order to identify elements that characterize the presence of affect and of interactivity in the offer of distance courses. The results show that although the professionals seek to provide different teaching strategies in order to contribute to the teaching and learning process of the students, there is still a long way to go in order to develop the potential of interactivity and affectivity in higher education and learning processes. With this research, we intend to seek subsidies for the educational act developed in the EaD courses to be permeated by care in relationships in order to give students a productive, pleasurable and instigating learning.